PENGARUH PENERAPAN PP 23 2018 TERHADAP KEPATUHAN PAJAK PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) - MARIA JESSICA SEPTIANI (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to test whether there is an effect of the implementation of Government Regulation no. 23 of 2018 of taxpayer compliance for Micro, Small and Medium Enterprises. This research method using quantitative descriptive method and primary data using a questionnaire. This study took a sample of 37 respondents taxpayer compliance for Micro, Small and Medium Enterprises at the Ruteng Pratama Tax Office, Manggarai, East Nusa Tenggara. The sampling technique was using purposive sampling technique. Data collection was carried out by distributing questionnaires in the form of google. The results showed that the implementation of PP 23 2018 has a positive effect on tax compliance of micro, small and medium enterprises.